Fashioning the body through women’s magazines: remaking the “modern Turkish woman” in the early republican period - Yakalı-Çamoğlu, Dikmen; Ataman, Bora (My University, 2011)
This study explores the newly constructed female identities and subjectivities of the early republican era in Turkey. Through a thematic analysis of four contemporary women’s magazines (Aile Dostu Ev-İş, Kadın-Ev and Asrın Kadını) it aims to examine how female bodies were refashioned in the magazines to fit the image of the newly constructed “woman of the republic”. It argues that the subjectivities offered by the magazines point to a dialogically constructed narrative identity which is not stable but fluid.
Keywords: Early republican period; narrative identity, Turkish women; Women’s Magazines.